A novel approach to offering additional genomic findings—A protocol to test a two‐step approach in the healthcare system. Issue 2 (18th February 2019) - Martyn, Melissa; Kanga‐Parabia, Anaita; Lynch, Elly; James, Paul A.; Macciocca, Ivan; Trainer, Alison H.; Halliday, Jane; Keogh, Louise; Wale, Janney; Winship, Ingrid; Bogwitz, Michael; Valente, Giulia; et al.
Abstract: Internationally, the practice of offering additional findings (AFs) when undertaking a clinically indicated genomic test differs. In the USA, the recommendation is to include analysis for AFs alongside diagnostic analysis, unless a patient opts‐out, whereas European and Canadian guidelines recommend opt‐in models. These guidelines all consider the offer of AFs as an activity concurrent with the offer of diagnostic testing. This paper describes a novel two‐step model for managing AFs within the healthcare system in Victoria, Australia and presents the study protocol for its evaluation. Adults who have received results of diagnostic whole exome sequencing undertaken within the healthcare system are invited to attend a genetic counseling appointment to consider reanalysis of their stored genomic data for AFs. The evaluation protocol addresses uptake, decision‐making, understanding, counseling challenges, and explores preferences for future models of care. Recruitment commenced in November 2017 and will cease when 200 participants have been approached. When the study is concluded, the evaluation results will contribute to the evidence base guiding approaches to counseling and models of care for AFs.